A Comparison of a Direct Electron Detector and a High-Speed Video Camera for a Scanning Precession Electron Diffraction Phase and Orientation Mapping. (December 2020) - MacLaren, Ian; Frutos-Myro, Enrique; McGrouther, Damien; McFadzean, Sam; Weiss, Jon Karl; Cosart, Doug; Portillo, Joaquim; Robins, Alan; Nicolopoulos, Stavros; Nebot del Busto, Eduardo; Skogeby, Richard
Abstract: Abstract : A scanning precession electron diffraction system has been integrated with a direct electron detector to allow the collection of improved quality diffraction patterns. This has been used on a two-phase α–β titanium alloy (Timetal® 575) for phase and orientation mapping using an existing pattern-matching algorithm and has been compared to the commonly used detector system, which consisted of a high-speed video-camera imaging the small phosphor focusing screen. Noise is appreciably lower with the direct electron detector, and this is especially noticeable further from the diffraction pattern center where the real electron scattering is reduced and both diffraction spots and inelastic scattering between spots are weaker. The results for orientation mapping are a significant improvement in phase and orientation indexing reliability, especially of fine nanoscale laths of α-Ti, where the weak diffracted signal is rather lost in the noise for the optically coupled camera. This was done at a dose of ~19 e − /Å 2, and there is clearly a prospect for reducing the current further while still producing indexable patterns. This opens the way for precession diffraction phase and orientation mapping of radiation-sensitive crystalline materials.